EVALUASI PROGRAM KEPENDUDUKAN KELUARGA BERENCANA DAN PEMBANGUNAN KELUARGA (KKBPK) DALAM MENEKAN ANGKA KEMATIAN IBU DI KOTA SEMARANG - Suryanto Muchlis; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Every year Indonesia’s population have increas is one of issues that must be considered by the Indonesian government. In addressing this issue, the government launched program the Family Planning and Family Development (KKBPK) program based on Law Number 52 Year 2009 on Population and Family Planning. One of the goals of this program is to reduce maternal mortality that has not been maximized in achievement. The problem raised in this research is how the implementation of Family Planning and Family Development (KKBPK) program to decreasing Maternal mortality rate? The purpose of this study is to evaluate and determine the factors that affect the implementation of KKBPK program to decreasing maternal mortality in the city of Semarang. This research is a type of qualitative research with descriptive approach. The results of this study indicate that the implementation of KKBPK program to decreasing maternal mortality has been running quite well based on the evaluation indicators including effectiveness, responsiveness, and accuracy. It is good enough proven with the implementation of the objectives of the program and felt well by the community. However, other indicators such as adequacy and smoothing are still not maximally proven to the uneven distribution of services provided and there are still problems related to insufficient funds and human resources. Factors that affect the implementation of KKBPK program include consistency of communication, human resources manager, disposition and organizational structure.